Torsion of wandering spleen, splenectomy and autotransplantation of splenic slices - Georgakis Ioannis; Papouis George; Pegios Athanasios; Vasiouris Panagiotis; Papamitsou Theodora (Elsevier, 2021)
The aim of this research is to highlight the peculiarity of the incident, to discuss the decision for the transplant splenic slices, and to present the positive results of this approach. The case includes a 14-year-old girl who was presented with atypical abdominal pain last year. Ultrasound imaging showed an abdominal mass in the left lower abdomen. Following that, a CT was performed where the wandering spleen was imaged. Doppler control revealed relatively good blood flow, but partial spleen stems rotation while blood tests revealed thrombocytopenia. However, during the surgical procedure, the spleen appeared 2 ½ times veering the axis of the vascular pedicle. The decision to splenectomy was made due to the presence of small clots during palpation of the vasculature, the appearance of thrombocytopenia, and the technically inadequate splenopexy due to the large vascular pedicle. Partial spleen auto-transplantation on the omental was subsequently carried out. The follow up provided satisfactory results in size and function. The wandering spleen has difficulty in its clinical diagnosis. Visual inspection could document the diagnosis. The suggested treatment is splenopexy, but in the decision for splenectomy, as in this case, with evidence of viable splenic tissue, the successful autotransplantation of splenic slices reduces the risk of splenectomy complications, such as the post-splenectomy sepsis.